Association of Cigarette Smoking with Aberrant Methylation of the Tumor Suppressor Gene RARβ2 in Papillary Thyroid Cancer - Kiseljak-Vassiliades, Katja; Xing, Mingzhao (Frontiers in Endocrinology, 2011)
Aberrant gene methylation is often seen in thyroid cancer, a common endocrine malignancy. Tobacco smoking has been shown to be associated with aberrant gene methylation in several cancers, but its relationship with gene methylation in thyroid cancer has not been examined. In the present study, we investigated the relationship between smoking of patients and aberrant methylation of tumor suppressor genes for TIMP3, SLC5A8, death-associated protein kinase, and retinoic acid receptor β2 (RARβ2) in papillary thyroid cancer (PTC), the most common type of thyroid cancer. The promoter methylation status of these genes was analyzed using quantitative real-time methylation-specific PCR on bisulfite-treated genomic DNA isolated from tumor tissues and correlated with smoking history of the patients. Among the four genes, methylation of the RARβ2 gene was significantly associated with smoking and other three genes showed a trend of association. Specifically, among the 138 patients investigated, 13/42 (31.0%) ever smokers vs. 10/96 (10.4%) never smokers harbored methylation of the RARβ2 gene (P = 0.003). This association was highly significant also in the subset of conventional variant PTC (P = 0.005) and marginally significant in follicular variant PTC (p = 0.06). The results demonstrate that smoking-associated aberrant methylation of the RARβ2 gene is a specific molecular event that may represent an important mechanism in thyroid tumorigenesis in smokers.